Capital letters in the codex "To" of the "Cantigas de Santa María" - Varela Barreiro, Xavier (Madrygal. Revista de Estudios Gallegos, 2014)
In this work we describe the use guidelines of capital letters into the codex To of the Cantigas de Santa María. We distinguish on it the employment of two well differenced use systems into word capitals and we put this fact in relation with the possibility that the preparation of the codex was made in two different moments. It was also useful to establish a first hypothesis about chronological relationships between the four codices of the Cantigas, and between these ones, the Cancioneiro da Ajuda and the Pergamino Vindel.
Keywords: capital letters; medieval; Galician; Cantigas de Santa María; Cancioneiro da Ajuda; Pergamiño Vindel.